Odpowiedzi

2009-05-25T21:08:55+02:00
X=-3-y
4(-3-y)-3y=-26
-12-4y-3y=-26
-7y=-26+1-7y=-14:(-7)
y=2
x+2=-3
x=-5


4x-3y=-26
x+y=-3/*(-4)
4x-3y=-26
-4x-4y=12
-7y=-14:(-7)
y=2
x+2=-3
x=-5
2009-05-25T21:09:24+02:00
1)
4x - 3y = -26
x + y = -3

4x - 3y = -26
x = -3-y

4(-3-y) - 3y = -26
x = -3-y

-12 - 4y - 3y = -26
x = -3-y

-7y = -14: (-7)
x = -3-y

y = 2
x = -3-2

y = 2
x = -5

2)
4x +3y = 10 *(-1)
3x + 4y = 11

-4x - 3y = -10
3x + 4y = 11

-7x - 7y = -21
-7(x + y) = -21 : (-7)
x + y = 3
x = 3 - y

4(3-y) + 3y = 10
12 - 4y + 3y = 10
-y = -2 :(-1)
y = 2
x = 3-2 = 1